Vaccine Hesitancy in Central Switzerland: Identifying and Characterizing Undervaccinated Children in a Pediatric Emergency Department - Anika Ménétrey; Markus A. Landolt; Michael Buettcher; Thomas J. Neuhaus; Leopold Simma (Pediatric Reports, 2023)
Vaccinations play an important role in the prevention of potentially fatal diseases. Vaccine hesitancy has become an important problem both in the public discourse and for public health. We aimed to identify and characterize this potentially unvaccinated or incompletely vaccinated group of children presenting to the pediatric emergency department (PED) of the tertiary children’s hospital in central Switzerland, a region that has anecdotally been claimed as a hotspot for vaccine hesitancy. All patients presenting to the PED (N = 20,247) between September 2018 and September 2019 were screened for their vaccination status and categorized as incomplete, unvaccinated, or fully vaccinated in a retrospective cohort study. Some 2.6% (n = 526) visits to the PED were not or incompletely vaccinated according to age, or their vaccination status was unknown. Most of the children in the cohort were not critically ill, and the minority had to be hospitalized. Undervaccinated patients were overrepresented in rural areas. Of all cohort visits, 18 (3.4%) patients received opportunistic vaccination in the PED. No cases of vaccine-preventable diseases were observed. In summary, incompletely vaccinated and unvaccinated status was less frequent than initially expected. The PED may play a role in increasing vaccination coverage by providing opportunistic vaccinations.